Free fall in crimson - MacDonald, John D. (John Dann), 1916-1986 (MacDonald, John D. (John Dann), 1916-1986. Travis McGee series., 1996)
This time out, McGee came close to losing his status as a living legend when he agreed to track down the killers who brutally murdered an ailing millionaire. For starters, he renewed an unfinished adventure with a famous-and oversexed-Hollywood actress, who led him into a very nasty nest of murderers involving a motorcycle gang, pornographic movies, and mad balloonists. And Mcgee relearned the old lesson-that only when he came close to the edge of death was he completely alive.